A comparison and identification study of dry sliding wear behaviour of Al/B4CP and Mg/B4CP composites for automobile disk brakes - Isin, O.; Istif, I.; Uzunsoy, Deniz; Guleryuz, F. (SAE International, 2014)
The brake friction materials in an automotive brake system play an important role in the overall braking performance of a vehicle. Metal Matrix Composites (MMCs) have been widely investigated and applied due to their advantages of improved strength, stiffness and increased wear resistance over the monolithic alloys in automobile industries. In this paper, Al/B 4CP and Mg/B4CP composites were compared to find a suitable candidate material for automotive disk brake application, in terms of wear behavior results of the materials. In addition, the experimental data was also used to model this behavior by identification. The measured tangential force was considered as the input parameter, whereas the weight loss as the output parameter. Preliminary results of this work showed that B4CP addition improved wear resistance of both aluminum and magnesium matrix composites. Additionally, the study pointed out that identified models provide a reliable and cost effective tool for wear prediction. Copyright © 2014 SAE International.
SAE 2014 World Congress and Exhibition -- 8 April 2014 through 10 April 2014 -- Detroit, MI -- 104424
Keywords: [No Kerywords]